Psalms 135 and 136: Exodus Motifs Contributing to Israelite Praise - Human, Dirk (Old Testament Essays, 2021)
The twin psalms 135 and 136 are both hymnic inspired texts with strong cultic features. In both psalms, exodus allusions and motifs play a role in the composers’ intention to build their own theological thrust. Both psalms display a plethora of resemblances regarding atmosphere, structure, themes, motifs, content and liturgical importance. Nonetheless, each of them radiates its own identity and theological intent. By reading these two psalms both separately and together, the common denominator places the focus on praise for the Israelite God, Yahweh. By identifying the exodus motifs and determining their function in each psalm, this article aims to contribute to the theological meaning of both psalms.
free
Keywords: African Contextual Hermeneutics; Exodus motifs; Ps 135; Ps 136; Twin psalms